Cyberspace and the state toward a strategy for cyber-power - Betz, David 1969-; Stevens, Tim (Adelphi (Series) (International Institute for Strategic Studies), 2011)
The major aim of Cyberspace and the State is to provide conceptual orientation on the new strategic environment of the Information Age. It seeks to restore the equilibrium of policy-makers which has been disturbed by recent cyber scares, as well as to bring clarity to academic debate on the subject particularly in the fields of politics and international relations, war and strategic studies. Its main chapters explore the impact of cyberspace upon the most central aspects of statehood and the state system-power, sovereignty, war, and dominion. It is concerned equally with practice as with theory and may be read in that sense as having two halves.